Collaborative Strategic Reading: A Comprehensive Way in Enhancing and Nurturing Literacy Culture - Esti Swatika Sari; Beniati Lestyarini; Liann Perez Camille Davalos Perez (Yayasan Keluarga Guru Mandiri, 2025)
This research aims to develop a literacy culture model based on Collaborative Strategic Reading. This strategy involves the collaboration of the school committee, headmasters, librarians, teachers, students, and parents using co-teaching alternatives and literacy materials. The research is designed based on the R2D2 development model, which includes three components: (1) define, (2) design and development, and (3) dissemination. This research occurred in SMP Negeri 3 Sewon, Bantul, Yogyakarta, where the data were collected using questionnaires, interviews, and tests. Descriptive qualitative analysis was used to analyze the data. The literacy culture model was developed based on co-teaching and collaborative strategic reading, which Moreillon introduced. These activities involve school committees, principals, librarians, teachers, students, and parents. This study produced a guidebook for implementing a literacy culture through reading and learning. Literacy Space's reading and learning activities provide a comfortable outdoor library with various books. An expert assessed product validation, and it was declared very feasible. The results showed that this model can be used well for literacy habituation. Thus, reading and learning activities effectively enhance and nurture literacy culture.